Voices of Africa: acoustic predictors of human male vocal attractiveness. (May 2017) - Šebesta, Pavel; Kleisner, Karel; Tureček, Petr; Kočnar, Tomáš; Akoko, Robert Mbe; Třebický, Vít; Havlíček, Jan
Abstract : Robust evidence shows that voice quality affects various social interactions, including mate preferences. Previous research found that male voices perceived as attractive are characterized by low voice pitch, lower or sexually typical formants and relatively high breathiness. These features tend to be seen as markers of an individual's quality as a potential mate. Although there are considerable differences between languages in vocal parameters that could influence the perceived attractiveness, the above-mentioned findings rely on research based mainly on participants from European or North American countries. In our study, we therefore tested the main acoustic predictors of vocal attractiveness using two male samples from Cameroon and Namibia. Standardized vocal recordings were then assessed for vocal attractiveness by a panel of female raters from the Czech Republic. Our results show that in the Cameroonian voices, fundamental frequency was strongly negatively associated with perceived vocal attractiveness. In the Namibian sample, however, it was not the fundamental frequency but lower mean formants and harmonics-to-noise ratio that were negatively associated with vocal attractiveness. This pattern may be partly attributed to differences in morphological characteristics such as the body mass index, indicating variation across individual populations. Highlights: Different acoustic parameters predicted attractiveness in two African samples. Fundamental frequency correlated with vocal attractiveness in Cameroonian men. Formants, harmonics-to-noise ratio and weight predicted attractiveness in Namibian men. Namibian participants showed relatively high levels of undernutrition. Differences between samples may thus be due to varying BMI.